Treatment of stage Ia and Ib mycosis fungoides with psoralen UVA monotherapy: an observational study in tertiary hospitals in the Canary Islands. (2nd April 2014) - Hernández, Zaida; Peñate, Yeray; Hernández‐Machín, Buenaventura; Pérez‐Méndez, Lina; Suárez‐Hernández, Jose; Hernández, Javier; Fernández‐de‐Misa, Ricardo
Abstract Background Mycosis fungoides (MF) is the most common form of primary cutaneous T cell lymphoma. Psoralen combined with ultraviolet A (PUVA) is a first‐line treatment for early‐stage disease. Objectives This study was conducted to assess the clinical effectiveness of and tolerance to PUVA monotherapy in MF. Methods We retrospectively reviewed the files of patients who received PUVA for stage I disease. The study included 31 patients, of whom 32% presented with stage Ia and 67% with stage Ib disease, and 68% presented with patch and 32% with plaque disease. All patients received treatment three times per week. Results Complete response (CR) was achieved in 71% of patients. The median cumulative dose of UVA at CR was 211.7 J/cm2. There was a significant difference in median cumulative dose at CR between patients with plaque and patch disease, respectively, but not between patients with stage Ia and Ib disease. Median disease‐free survival (DFS) was 230 weeks. Patients with patch disease achieved longer DFS than those with plaque disease (P = 0.004), although DFS was similar in stage Ia and Ib patients. Of the patients who received maintenance therapy, 58% relapsed. Univariate analysis showed patch disease to be a predictive factor for CR, but no predictors of relapse were identified. A total of 71% of patients developed clinical adverse reactions. Conclusions Psoralen with UVA is a safe and effective treatment for early‐stage MF. Patch disease responds more favorably than plaque disease and is associated with a longer period of DFS. Maintenance treatment does not appear to reduce recurrence. Current evidence suggests that the proposed revision to the classification of MF, which takes into account the extent and type of disease, more accurately predicts response to PUVA.